2014
DOI: 10.1016/j.cell.2014.07.049
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Control of Social versus Repetitive Self-Grooming Behaviors by Separable Amygdala Neuronal Subsets

Abstract: SUMMARY Animals display a range of innate social behaviors that play essential roles in survival and reproduction. While the medial amygdala (MeA) has been implicated in prototypic social behaviors such as aggression, the circuit-level mechanisms controlling such behaviors are not well understood. Using cell-type specific functional manipulations, we find that distinct neuronal populations in the MeA control different social and asocial behaviors. A GABAergic subpopulation promotes aggression and two other soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
341
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(369 citation statements)
references
References 65 publications
21
341
6
1
Order By: Relevance
“…6B, 7A). Interestingly, we have recently observed similar results following optogenetic stimulation of GABAergic neurons in the medial amygdala (Hong et al 2014), a structure that projects indirectly to VMHvl (Canteras et al 1992(Canteras et al , 1995Swanson 2000). We have also observed scalable control of different defensive behaviors-avoidance, freezing, and flight-following stimulation of a different subpopulation of VMH neurons located in its dorsomedial subdivision (Kunwar et al 2015).…”
Section: Scalable Control Of Social Behavior By Vmhvl Esr1 1 Neuronssupporting
confidence: 56%
See 1 more Smart Citation
“…6B, 7A). Interestingly, we have recently observed similar results following optogenetic stimulation of GABAergic neurons in the medial amygdala (Hong et al 2014), a structure that projects indirectly to VMHvl (Canteras et al 1992(Canteras et al , 1995Swanson 2000). We have also observed scalable control of different defensive behaviors-avoidance, freezing, and flight-following stimulation of a different subpopulation of VMH neurons located in its dorsomedial subdivision (Kunwar et al 2015).…”
Section: Scalable Control Of Social Behavior By Vmhvl Esr1 1 Neuronssupporting
confidence: 56%
“…The foregoing data indicate that artificial activation of VMHvl (and MeApd) neurons at different intensities can evoke different types of social behavior at different thresholds (Hong et al 2014;Lee et al 2014) and that the average spiking rate among VMHvl neurons increases as animals progress from investigative to attack behavior (Lin et al 2011;). Together, these findings raise the intriguing possibility that VMHvl encodes the intensity of an escalating state of arousal, motivation, or drive, in a graded manner according to its level of activity (Fig.…”
Section: Social Behavior Control Centers: Rheostats or Switches?mentioning
confidence: 99%
“…On the other hand, ERα silencing in the medial amygdala (MeA) did not affect either behavior (9), contrary to our predictions. Numerous studies have shown that neurons in the MeA express a high level of ERα (10)(11)(12) and play a role in the facilitation of both male sexual and aggressive behaviors (13)(14)(15)(16)(17)(18). However, consistent with our findings, Paisley et al (19) reported that the site-specific suppression of ERα with antisense in the MeA did not affect the expression of sexual behavior in gonadally intact male rats.…”
contrasting
confidence: 43%
“…Our findings showing a reduced number of MeA neurons in the MeA-αERKD group suggest that the presence of ERα is required for testosterone to masculinize the neuronal number in the MeA during the pubertal period. The importance of the MeA in the regulation of male-type social behaviors has been demonstrated in numerous studies (13)(14)(15)(16)(17)(18). Particularly, the MeA plays a significant role in chemosensory information processing (15,16,33,34) as part of the social behavior network in the CNS (35).…”
Section: Discussionmentioning
confidence: 99%
“…Several cortical and subcortical brain regions have been implicated in controlling social behavior, such as the prefrontal cortex, amygdala, striatum, dorsal raphe, and hypothalamus (Gingrich et al 2000;Young et al 2001;Leypold et al 2002;Robinson et al 2002;Liu and Wang 2003;Young and Wang 2004;Curtis and Wang 2005;Aragona et al 2006;Lin et al 2011;Robinson et al 2011;Dölen et al 2013;Yang et al 2013;Felix-Ortiz and Tye 2014;Hong et al 2014;Unger et al 2015). In rodents, the majority of these studies have focused on sociosexual behaviors, such as pair bonding, aggression, and other behaviors related to sexual competition.…”
mentioning
confidence: 99%